Inventories and concentration profiles of 137Cs in undisturbed soils in the northeast of Buenos Aires Province, Argentina - Montes, María Luciana (2012)
Inventories and vertical distribution of 137Cs were determined in La Plata region undisturbed soils, Argentina. A mean inventory value of 891 ± 220 Bq/m2 was established, which is compatible with the values expected from atmospheric weapon tests fallout. The study was complemented with pH, organic carbon fraction, texture and mineralogical soil analyses. Putting together Southern Hemisphere 137Cs inventory data, it is possible to correlate these data with the mean annual precipitations. The large differences in 137Cs concentration profiles were attributed to soil properties, especially the clay content and the pH values. A convection–dispersion model with irreversible retention was used to fit the activity concentration profiles. The obtained effective diffusion coefficient and effective convection velocity parameters values were in the range from 0.2 cm2/y to 0.4 cm2/y and from 0.23 cm/y to 0.43 cm/y, respectively. These data are in agreement with values reported in literature. In general, with the growth of clay content in the soil, there was an increase in the transfer rate from free to bound state. Finally, the highest transfer rate from free to bound state was obtained for soil pH value equal to 8.